Pengaruh Penggunaan Media Pembelajaran Berbasis Video terhadap Hasil Belajar Siswa Kelas IV pada Mata Pelajaran Matematika di SDN Undaan Kidul 3 Demak - Maulida, Lia Khusna; Nabila, Putri Zidni; Arrodli, Muhammad Asro; Amaliyah, Fitriyah (Indo-MathEdu Intellectuals Journal, 2024)
Mathematics is a science that is obtained through thinking and reasoning. However, Very often, elementary school students have difficulty understanding math lessons. Thus, Teachers must use creativity and imagination while using a range of instructional resources and media. Video learning is one example. The purpose of this study is to ascertain the effects of using video-based learning resources on the mathematical learning outcomes of students at SDN Undaan Kidul 3 Demak. Quantitative Pre-Experimental was used with the design of one pre-test and post-test group, and was carried out on grade IV students at SDN Undaan Kidul 3 Demak, with a sample consisting of 15 students, which included 5 female students and 10 male students.  The data instruments used include tests (pretest and postest), questionnaires, interviews, observations, and documentation. The results of this study show that the use of video-based learning media improves students' learning ability, this is characterized by an increase in pretest and posttest to a higher level from the average score of 66 to 76.67. Therefore, Using video-based learning resources is crucial for raising elementary school pupils' mathematics proficiency